Seasonal effects on growth, digestibility, and metabolism of preweaning dairy calves in the southeastern United States - Ansley M. Roper; Ruth M. Orellana Rivas; Jing Gao; Thiago N. Marins; C.G. Savegnago; Thalyane Rodrigues; Victor H.L.R. Melo; Diego Ferreira de Araújo; Juliana Goncalves de Souza; Pedro Melendez; John K. Bernard; Sha Tao (Journal of Dairy Science)
ABSTRACT: The aim of the current study was to evaluate seasonal effects on growth, digestibility, and metabolism of dairy calves in Georgia. Holstein calves (n = 48 per season) were enrolled at 7 d of age (DOA) from June to Aug (defined as summer, BW = 40 ± 4 kg) and from Nov to Jan (defined as winter, BW = 42 ± 4 kg). Similar general management and feeding practices were applied to calves in both seasons. Calves were housed in individual polyethylene hutches with sand bedding. Starting at 2 DOA, calves were fed a milk replacer (MR) containing 26% protein and 17% fat (0.65 or 0.76 kg of DM/d and mixed with warm water to reach 12.5% solids) and calf starter (CS) was offered ad libitum. Weaning began at 43 DOA by reducing MR 50% until 49 DOA when MR feeding ceased. Calves remained enrolled until 63 DOA. Calf starter intake was recorded daily. Ambient temperature (AT) and relative humidity (RH) were recorded hourly. Rectal temperature and respiration rate were assessed 3×/wk and BW was measured weekly. Blood was collected to analyze metabolites and insulin at 3, 7, 14, 21, 28, 35, 42, 49, 56, and 63 DOA. The apparent total-tract digestibility of nutrients was measured during both the pre- (14.9–17.9 DOA) and postweaning (51.0–54.0 DOA) periods. The MIXED procedure of SAS was used to analyze repeated measures data. Season, time, and their interactions were included as the fixed effects. The CV of hourly AT or RH within a day was calculated as a proxy of within-day variation. The CV of daily average AT or RH within a week was used as the proxy of day-to-day variation. Linear regression analysis between ADG and environmental parameters was performed using the GLM procedure. Summer months had greater AT (27°C vs. 13°C) but similar RH (83% vs. 81%) relative to winter months, respectively. Rectal temperature and respiration rate were higher during the summer compared with winter. Season had no effect on CS intake before weaning, but summer calves had greater CS intake at 9 wk of age compared with winter calves. No seasonal effect was observed for BW, but summer calves had greater ADG at 3, 5, and 9 wk of age. A negative relationship (R2 = 0.11) between preweaning ADG and within-day AT variation was observed during winter, whereas during the summer day-to-day AT variation was negatively associated with preweaning ADG (R2 = 0.06). Compared with calves raised during winter, calves raised in summer had lower apparent total-tract digestibility of DM, OM, and CP during the preweaning period. Furthermore, summer calves had lower circulating glucose before and after weaning and lower blood BHB concentrations following weaning compared with calves raised in winter. In conclusion, in Georgia, the within-day and day-to-day AT variations affect preweaning calf growth, and calves raised during summer had lower nutrient digestibility and altered metabolism relative to calves raised in winter.